2018
DOI: 10.1186/s40645-018-0176-7
|View full text |Cite
|
Sign up to set email alerts
|

Construction of perfectly continuous records of physical properties for dark-light sediment sequences collected from the Japan Sea during Integrated Ocean Drilling Program Expedition 346 and their potential utilities as paleoceanographic studies

Abstract: Establishment of sedimentary sequence is essential for the interpretation of the sedimentary records. Integrated Ocean Drilling Program (IODP) Expedition (Exp.) 346 drilled high-quality sediment archives with more than three holes each at nine sites that enable us to establish continuous sedimentary sequences through splicing technique. After extensive efforts to replace the disturbed, missed, or duplicated intervals found in spliced sediment sequences constructed onboard during IODP Exp. 346 to the correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 20 publications
1
49
0
Order By: Relevance
“…Previous studies have demonstrated that the darklight layers in sediments from deeper sites can be correlated across the JS (e.g., Tada et al 1992;Nakajima et al 1996). This is also the case for the six deeper sites of Expedition 346, which are readily correlated over the past 1.5 Myr (Tada et al 2018 Fig. 1 Locations of sites drilled during IODP Expedition 346 in the Japan Sea and East China Sea.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Previous studies have demonstrated that the darklight layers in sediments from deeper sites can be correlated across the JS (e.g., Tada et al 1992;Nakajima et al 1996). This is also the case for the six deeper sites of Expedition 346, which are readily correlated over the past 1.5 Myr (Tada et al 2018 Fig. 1 Locations of sites drilled during IODP Expedition 346 in the Japan Sea and East China Sea.…”
Section: Introductionmentioning
confidence: 64%
“…During this re-evaluation, a stratigraphical gap and repeated successions were found in the original shipboard splice (Irino et al 2018). Detailed inter-hole correlation and revision of the shipboard splices for Sites U1426 and U1427 are presented by Irino et al (2018). The depth-scale for the revised splice section is expressed as "patched_CCSF-D" in this study.…”
Section: Sediment Coresmentioning
confidence: 92%
See 2 more Smart Citations
“…Tada et al (1999) suggested that changes in freshwater discharge from the Changjiang and Yellow Rivers, and consequent changes in the spatial extent of the nutrient-rich and low-salinity ECS coastal water, were the main cause of changes in a nutrient influx into the Japan Sea, and primary production there during MIS 3. The increased influence of the ECS coastal water not only enhanced primary productivity, but also reduced deep-water ventilation, leading to the development of the anoxic bottom waters and deposition of the dark layers (Tada et al 1999;Irino et al 2018). This hypothesis can be tested by comparing the temporal variations in the SSS in the northern ECS with L* of the hemipelagic sediments in the Japan Sea (Watanabe et al 2007).…”
Section: Regional and Global Factors Affecting The Japan Sea Recordsmentioning
confidence: 99%